Synthesis of Graphene Oxide-Polystyrene Graft Polymer Based on Reversible Addition Fragmentation Chain Transfer and Its Effect on Properties, Crystallization, and Rheological Behavior of Poly (Lactic Acid) - Li Yang; Weijun Zhen (Advances in Polymer Technology)
Graphene oxide-polystyrene graft polymer (SGO-PS) was prepared by reversible addition-fragmentation chain transfer radical polymerization method. Orthogonal experiments indicated that the optimum synthesis reaction conditions for SGO-PS were as follows: the millimole ratio of chain transfer agent to initiator was 0.15 : 0.3, and the amount of styrene was 8 mL at 80°C for 12 hours. The products were characterized by Fourier transform infrared spectroscopy and thermal weightlessness analysis, and the highest grafting rate of SGO-PS was 62.46%. Then, PLA/SGO-PS nanocomposites were prepared using SGO-PS as fillers by melt intercalation method, and its crystallinity, mechanical properties, and thermal stability were significantly improved. Compared with pure PLA, the crystallinity of PLA/SGO-PS (0.3 wt%) nanocomposites was increased by 5 times. Multiple melting behavior tests showed that the introduction of SGO-PS caused the PLA molecular chain to be discharged into the unit cell in time, and the melting temperature shifted to a higher temperature, which ultimately made the grain structure of PLA composites more complete and stable than pure PLA. The rheological performance test showed that the uniform dispersion of SGO-PS in the PLA matrix inhibited the free movement of the PLA molecular chain and caused higher flow resistance, resulting in an increase in the complex viscosity, storage modulus, and loss modulus of PLA/SGO-PS.